Swimming Exercise Alleviated Insulin Resistance by Regulating Tripartite Motif Family Protein 72 Expression and AKT Signal Pathway in Sprague-Dawley Rats Fed with High-Fat Diet - Jie Qi; Bo Yang; Cailing Ren; Jian Fu; Jun Zhang (Journal of Diabetes Research)
We aimed to investigate whether swimming exercise could improve insulin resistance (IR) by regulating tripartite motif family protein 72 (TRIM72) expression and AKT signal pathway in rats fed with high-fat diet. Five-week-old rats were classified into 3 groups: standard diet as control (CON), high-fat diet (HFD), and HFD plus swimming exercise (Ex-HFD). After 8 weeks, glucose infusion rate (GIR), markers of oxidative stress, mRNA and protein expression of TRIM72, protein of IRS, p-AKTSer473, and AKT were determined in quadriceps muscles. Compared with HFD, the GIR, muscle SOD, and GSH-Px were significantly increased (p<0.05, resp.), whereas muscle MDA and 8-OHdG levels were significantly decreased (p<0.05 and p<0.01) in Ex-HFD. Expression levels of TRIM72 mRNA and protein in muscles were significantly reduced (p<0.05 and p<0.01), whereas protein expression levels of IRS-1, p-AKTSer473, and AKT were significantly increased in Ex-HFD compared with HFD (p<0.01, p<0.01, and p<0.05). These results suggest that an 8-week swimming exercise improves HFD-induced insulin resistance maybe through a reduction of TRIM72 in skeletal muscle and enhancement of AKT signal transduction.